Distribution, effect and utilization of Mikania micrantha on livelihood: Case study of Janakauli buffer zone community forest of Chitwan National Park - Shrestha, Sami (Journal of Agriculture and Natural Resources, 2019)
Forest of lowlands is heavily impacted by invasive plants species, particularly Mikania micrantha which is also considered as one of the most invasion species. So, it became essential to understand effects of Mikania to user and indigenous vegetation; however the studies were confined to appraising the distribution, effect and utilization of Mikania micrantha on the livelihood of buffer zone of the Chitwan National Park. Vegetation survey, key informant interview, focus group discussion, direct observation and stratification were conducted. GPS points were recorded and the distribution map of Mikania was made by using ArcView GIS 10.1 and has been found throughout the Community Forest. Regression analysis showed that the number of plant regeneration of native tree species decreases by 0.530 unit with every 1 unit increment in Mikania crown cover. The study used a questionnaire survey to 118 households in the CNP of Nepal. The results indicate that the invasion of M. micrantha have negative effects on the community livelihood in the study area. Basic forest products such as fodder and fuel wood have become scarce as a result of reduction in the native plants. Only 6.78% of the users utilize Mikania for household purpose like briquettes fuel, fodder, medicine and manure. The losses of other plant species have severe effect to biodiversity so control measure with utilization should be taken as the most needed action. Regular assessment and monitoring of Mikania effect is necessary to understand the problem and its impact on biodiversity of lowland forest of Nepal.